Expert Perspectives On Clinical Challenges: Expert Perspectives: Challenges in Scleroderma. Issue 9 (9th August 2020) - Simms, Robert W.
Abstract : You are consulted to evaluate a 56‐year‐old woman with known Raynaud's phenomenon, finger swelling of several; months' duration, and new hypertension with a blood pressure of 160/100 mm/Hg. She also reports progressive shortness of breath. Physical examination reveals telangiectasias, sclerodactyly, and proximal skin sclerosis (thick shiny skin on the chest and upper arms), and bibasilar crackles are found on chest examination. Laboratory tests reveal evidence of microangiopathic hemolytic anemia, thrombocytopenia, and elevation of the serum creatinine level (previously normal), and chest computed tomography shows evidence of ground‐glass opacification in both lower lung fields.